2014
DOI: 10.1080/15389588.2014.942418
|View full text |Cite
|
Sign up to set email alerts
|

Safety Impacts of Red Light Cameras at Signalized Intersections Based on Cellular Automata Models

Abstract: RLCs are found to have a mixed effect on accident risk at signalized intersections: crossing collisions are reduced, whereas rear-end collisions may increase. The specially developed CA model is found to be a feasible safety assessment tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Ahmed and Abdel-Aty [21] analyzed traffic accidents at intersections and found that traffic violation monitoring would reduce left-turn traffic accidents but increase traffic accidents in other directions. Chai et al [22] believed that traffic violation monitoring has different effects on different types of traffic accidents. Traffic violation monitoring reduces the occurrence of collision accidents, but the probability of rear-end accidents increases.…”
Section: Introductionmentioning
confidence: 99%
“…Ahmed and Abdel-Aty [21] analyzed traffic accidents at intersections and found that traffic violation monitoring would reduce left-turn traffic accidents but increase traffic accidents in other directions. Chai et al [22] believed that traffic violation monitoring has different effects on different types of traffic accidents. Traffic violation monitoring reduces the occurrence of collision accidents, but the probability of rear-end accidents increases.…”
Section: Introductionmentioning
confidence: 99%
“…Model was calibrated and validated with field data. Model was able to predict delays but saturation flows were predicted with 30% variabilitylane and direction[37]2opensimulation of heterogeneous traffic at simple X and T‐intersectionsmodel was validated with data of Dublin[61]1periodicbesides free flow, jamming and platoon phases in fundamental diagram, a fourth phase is visible and vanishes when probability of priority is 0.5[62]1periodicmodified NS model, simulated urban two‐way traffic having one lane both sides, added additional movement rule and grid‐lock prevention rulefundamental diagrams were validated[38, 63]1opensimulated right‐turn vehicular interactions for Singapore. Model was validated with field data.…”
Section: Literature Review Of the Ca Model At The Intersectionmentioning
confidence: 99%
“…A straightforward way is to use RLR cameras to detect RLR behaviors, and the traffic police will give a corresponding penalty related to the severity of the RLR behavior, and much research has shown that RLR cameras significantly reduce RLR frequency [10,11]. However, some researches argue that RLR cameras may increase rear-end crashes [12]. Hence, it is not enough to only use enforcement methods for RLR reduction.…”
Section: Introductionmentioning
confidence: 99%